2012
DOI: 10.5032/jae.2012.03014
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Immediacy and Audio/Video Technology Use in Online Course Delivery: What Do University Agricultural Education Students Think?

Abstract: As demand for online course delivery increases, it is imperative that those courses be delivered in an effective and efficient manner. While technologies are offering increasingly new and innovative tools to deliver courses, it is not known which of these tools are perceived as useful and beneficial by university agricultural education students. This study sought to measure the impact of using an audio/video communication tool (Jing™) within the online classroom environment in an effort to document the tool’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Settle et al (2012) found prior association with social media in an educational setting led to more positive perceptions of social media within education. Due to the large percentage of students who routinely use Facebook™, there are more opportunities to connect students to the educational content through social media (Murphrey, Arnold, Foster, & Degenhart, 2012). Settle et al (2011) found that students believed it was probably important to know how to use online forums, video-sharing sites and blogs for future careers, with micro-blogs and social networking sites other than Facebook™.…”
mentioning
confidence: 99%
“…Settle et al (2012) found prior association with social media in an educational setting led to more positive perceptions of social media within education. Due to the large percentage of students who routinely use Facebook™, there are more opportunities to connect students to the educational content through social media (Murphrey, Arnold, Foster, & Degenhart, 2012). Settle et al (2011) found that students believed it was probably important to know how to use online forums, video-sharing sites and blogs for future careers, with micro-blogs and social networking sites other than Facebook™.…”
mentioning
confidence: 99%
“…Web-based environments, though they do not involve face-to-face interaction, were also important contexts that led to interaction. 16 , 19 , 40 , 41 , 47 , 56 , 72 , 87 , 93 , 109 , 126 , 127 , 130 , 142…”
Section: Antecedentsmentioning
confidence: 99%
“…In many projects, video has replaced traditional training and serves as a stand-alone knowledge and innovation dissemination approach. Video-mediated training has a strong potential to overcome information inequality (Bery 2003;Lie & Mandler 2009;Zossou et al, 2010) again this alleviate the fears as shown by Murphrey et al (2012). Agricultural science teachers use photocopying machine (16%) and public address system (17%) mostly to reach their students.…”
Section: * Multiple Responsesmentioning
confidence: 99%
“…Onyango (2000) summed up the magnitude of the political problems saying that the policies have tended to fail in Africa because there has been no thread of continuity or review process in all policy matters. Murphrey, Arnold, Foster and Degenhart (2012) stated that research is needed to determine how technology can be used to improve learning and the learning environment, especially from the learner's perspective. Roades, Irani, Telg and Myers (2008) reported a majority of college of agriculture students own computer and are users of audio/video technology, which indicate these types of technology could be a viable teaching tool.…”
Section: Introductionmentioning
confidence: 99%